2009
DOI: 10.1097/aln.0b013e3181ac1d7b
|View full text |Cite
|
Sign up to set email alerts
|

End-tidal Sevoflurane and Halothane Concentrations during Simulated Airway Occlusion in Healthy Humans

Abstract: During simulated airway occlusion in healthy volunteers, the end-tidal concentration of halothane falls more rapidly than that of sevoflurane. Halothane may therefore lead to more rapid awakening, compared with sevoflurane, should the airway obstruct during an inhalational induction of anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…One study showed that sevoflurane (with its lower solubility and slower redistribution) was found to decline three times slower than halothane, resulting in slower wake-up time. (61) Another study showed faster wake-up time with sevoflurane.…”
Section: Awake or Asleep Intubationmentioning
confidence: 99%
“…One study showed that sevoflurane (with its lower solubility and slower redistribution) was found to decline three times slower than halothane, resulting in slower wake-up time. (61) Another study showed faster wake-up time with sevoflurane.…”
Section: Awake or Asleep Intubationmentioning
confidence: 99%
“…Although modern practice suggests sevoflurane is now the drug of choice for inhalational induction, studying the influence of blood solubility during simulated airway occlusion in healthy volunteers suggests otherwise. The end-tidal concentration of halothane may fall more quickly than that of sevoflurane [26], and halothane compared with sevoflurane may thus lead to a quicker awakening [26]. The application of continuous positive airway pressure (CPAP) and positive end-expiratory pressure (PEEP) when assisting ventilation with bag and mask may help relieve any obstruction by acting as a pneumatic splint.…”
Section: Inhalational Inductionmentioning
confidence: 99%